Design of a segment-type ring burst test device to evaluate the pressure resistance performance of composite pressure vessels. (15th June 2020) - Kim, Woe Tae; Kim, Seong Su
Abstract: Composite pressure vessels used to store fuel gases or liquids should exhibit mechanical properties that allow them to withstand high pressures without being damaged. Therefore, an accurate measurement of their mechanical properties is essential prior to their commercial release. A segment-type ring burst test is a facile method to determine the burst pressure; however, the application of uniform pressure to the specimen remains a crucial issue to be addressed. Therefore, in this study, the conventional ring burst test device is modified to enhance the uniformity of pressure applied to the specimen. First, the equation of load transfer ratio from the applied load is derived. To verify the uniformity of pressure in the ring burst test device, the hoop strain distribution of the ring specimen is compared with that of the hydraulic pressure test obtained from the theoretical equation and finite element analysis. Based on the result, the number of segments is determined, and a polytetrafluoroethylene sheet is placed between the segments and the specimen to reduce the discrepancy of the hoop strain. Furthermore, to verify the reliability of the redesigned test device, the strain distribution and fracture behavior are assessed using the digital image correlation method and a high-speed camera.